EPPO, Conflicts and the €100,000 Financial Threshold: 'A Means to Circumvent Investigation?' - Andrew Zuidema (Utrecht Law Review)
The European Public Prosecutor’s Office (EPPO) is an independent public prosecution office of the EU responsible for PIF Offences. The EPPO has primacy over PIF Offences: if a criminal case is within its competence it has the power to handle the case over other authorities. The EPPO Regulation requires the EPPO to initiate investigations within its competence if no other authority is conducting a criminal investigation. This prevents impunity for suspects of PIF Offences, and prevents in concreto negative conflicts of competence. However, there is uncertainty whether a financial threshold of €100,000 may be applicable to initiation situations. This threshold, while applicable in special cases, is not a competence criterion, and there are safeguards to prevent in concreto negative conflicts from occurring or persisting when it is used outside of initiation situations. While this financial threshold is a useful tool for the EPPO in certain circumstances, it is inapplicable to initiation situations due to the EPPO Regulation’s prevention of in concreto negative conflicts of competence.